ANALISIS PERBANDINGAN METODE BIAYA TRADISIONAL DAN METODE ACTIVITY BASED COSTING DALAM PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA MIKRO KECIL MENENGAH TOKO KARYA OLI - Nur Wulanda, Elvira; Isneli, Yeni; Juliano, Michel (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
Calculation of Cost of Production is a calculation of all production costs that must be incurred to process a raw material to become finished goods or process services within a certain period of time. Considering the importance of calculating the cost of production, it has led to a new method in calculating the cost of production, known as the Activity-Based Costing (ABC) System. Toko Karya Oli currently still uses the traditional system in determining its cost. Based on the results of the study, the following conclusions can be drawn: Activity Based Costing is an accounting method that calculates each cost incurred in each activity with a different allocation for each activity. ABC is more focused on costs on products that are sourced from the process during production. While the traditional calculation method is a calculation based on the stage of production of goods in each unit. Calculation of the cost of production using the Activity Based Costing method provides a large profit calculation compared to using traditional calculation methods. This is because the Activity Based Costing method calculates every detail issued with a different allocation for each activity.